Twenty-Five Years of Cancer Immunogene Therapy: Anti - Gene IGF-I Approach. Issue 4 (2019) - Trojan, Jerzy; Gonzalez, Gonzalez; Hor, Maciej Bierwagen; Sierzega, Tatiana Castillo; Popiela, Zbigniew Wolski; Lone, Heliodor Kasprzak; Shevelev, Alexander; Ayala, Adis; Ly, Adama; Junkiert, Anna; Pan, Yuexin X.; Wei, Ming X.; et al.
No abstract available